PBL 在教學實習上的應用成效與困境之研究 A Study of Effects and Limitations of the Application of Problem-Based Learning on a Student Teaching Curriculum - 張德銳 Derray Chang; 林縵君 Man-Chun Lin (National Changhua University of Education, 2016)
我國的師資職前教育長期以來較重視理論知識的傳授，卻輕實務訓練與問題解決能力的培養，為此，個案學校以問題導向學習（Problem-Based Learning，簡稱PBL）融入教學實習課程中，以培養師資生的批判思考與問題解決能力。本研究以修習教學實習課程之師資生為調查對象，並透過問卷調查及焦點團體訪談，以探討師資生在PBL 學習經驗上的困境或限制。研究結果顯示，PBL 融入教學實習課程確實能促進師資生整合教學理論知識並加以實踐。而藉由案例問題，不僅增進師資生判思考與問題解決的能力，更間 接提升其教學信心與效能感。PBL 融入教學實習課程的困難在於案例銜接不易、教學經驗不足、討論時間不夠及社會賦閒現象的產生等。 Pre-service teacher education in Taiwan tends to pay more attention to teaching theoretical knowledge, and less to practical training and problem-solving ability. In view of this, the case school has been applying problem-based learning (PBL) in its student teaching curriculum to enhance the capability for critical thinking and problem solving for pre-service teacher education students. Through a focus group interview and questionnaire survey, the study focuses on the students who took the student teaching curriculum and aims to explore the challenges and limits of PBL learning experiences. The study results showed that indeed the inclusion of PBL in the student teaching curriculum facilitated students' integration of theoretical knowledge and practice. The discussion of problems introduced in the case studies not only enhanced students' critical thinking, problem solving abilities, confidence, and self-efficacy. However, the challenges for applying PBL in the student teaching curriculum lay in the toughness of case transformation, students' lack of teaching experiences, shortage of discussion time, and the phenomenon of social loafing.